CASE STUDY: MIDWIFERY CARE FOR GENDER EQUALITY IN PREGNANCY PLANNING, DELI SERDANG - Zai, Wempy Parisca; Dewi, Eva Ratna; Jemalemna; Berutu, Imel; Gulo, Wendi Idol Sryningsih (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
Background: Gender equality in household role division, particularly husband involvement in pregnancy planning, plays an important role in maternal physical and psychological readiness before pregnancy. A preliminary survey in Dusun II, Bangun Rejo Village, Tanjung Morawa Subdistrict, Deli Serdang Regency, identified one family showing an imbalance in gender equality practices, where Mrs. E (32 years old) reported that decisions regarding pregnancy planning were mostly dominated by her husband, with limited involvement in determining her own readiness, causing fatigue and anxiety. Objectives: This study aimed to provide community midwifery care for Mrs. E, 32 years old, related to gender equality in pregnancy planning in Dusun II, Bangun Rejo Village, in 2026. Methods: This was a descriptive case study using the seven-step midwifery management approach by Helen Varney, covering data collection, problem identification, anticipation of potential problems, immediate action, planning, implementation, and evaluation. Data were obtained through interviews and home visits conducted from February 9 to May 2, 2026. Results: The initial assessment showed decision-making dominated by the husband and limited involvement of the wife, accompanied by anxiety. After health education and counseling were provided, three follow-up visits showed progressive improvement: communication between the couple improved, the husband became more actively involved in discussions and pre-pregnancy health checks, and by the final visit the couple had fully shared decision-making in pregnancy planning. Conclusions: Community midwifery care effectively improved the couple’s understanding and practice of gender equality, strengthened communication, increased husband involvement, and created a more harmonious and supportive family relationship in preparing for pregnancy.